2021
DOI: 10.1142/s0218126622500025
|View full text |Cite
|
Sign up to set email alerts
|

GSTChain: A Blockchain Network Application for the Goods and Services Tax

Abstract: In 2017, the Government of India launched the goods and services tax (GST), referred to as “one tax, one nation, one market”. This tax all Indian businesses are subject to this tax. GST was framed with the objective of bringing tax handling for all businesses onto a single platform and developing a transparent and effective system in which all businesses will pay taxes. This paper identifies and addresses GST implementation challenges and proposes a solution, GSTChain, using blockchain network technology. Curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…By employing the power of a distributed ledger, blockchain can simplify firms' compliance requirements and aid in tax revenue collection. Blockchain technology can provide high transparency and security, enhancing the GST system's trust and compliance and ensuring that the system is free of fraudulent activities [140].…”
Section: G Goods and Service Tax (Gst)mentioning
confidence: 99%
“…By employing the power of a distributed ledger, blockchain can simplify firms' compliance requirements and aid in tax revenue collection. Blockchain technology can provide high transparency and security, enhancing the GST system's trust and compliance and ensuring that the system is free of fraudulent activities [140].…”
Section: G Goods and Service Tax (Gst)mentioning
confidence: 99%
“…They solved the problem and developed an end-to-end solution by exploring intelligent method and the blockchain management for better matching of the relations knowledge graphs set. Pasha et al [25] addressed and identified GST implementation and proposed , GSTChain, as a solution using blockchain network technology. The main objective behind such innovation was to make tax collection transparent and efficient for the government.…”
Section: Scope Of the Surveymentioning
confidence: 99%